Some Tauberian Remainder Theorems for Holder Summability - Totur, Umit; Okur, Muhammet Ali (Mathematical Modelling and Analysis, 2015)
In this paper, we prove some Tauberian remainder theorems that generalize the results given by Meronen and Tammeraid [Math. Model. Anal., 18(1):97– 102, 2013] for Holder summability method using the notion of the general control modulo of the oscillatory behaviour of nonnegative integer order.